Assessing Knowledge and Attitudes Towards Anemia Among Adolescent Girls at Pesantren Nur Al-Iman Moncongloe, Maros Regency - Awaru, Andi Fatwa Tenri; Nur Asmi (Jurnal Gizi dan Kesehatan Keluarga, 2024)
One group that is vulnerable to anemia is adolescent girls and this is evidenced by the high prevalence of iron deficiency anemia in adolescent girls. It impacts on decreased work productivity or academic ability at school due to lack of passion for learning and concentration and many more unfavorable effects. The problem of anemia in adolescent girls is caused by a lack of knowledge, attitudes and skills of adolescents due to lack of information delivery, lack of concern of parents, communities and governments for adolescent health and not optimal adolescent health services. , the purpose of this study is to see the level of understanding of adolescent girls about the incidence of anemia at the Al Iman Moncongloe Islamic Boarding School. This type of research uses descriptive methods to determine the description of the level of knowledge of adolescent girls about anemia at Pondok Pesantren Nur Al-Iman Moncongloe Kab. Maros. The sampling technique of this study was accidental sampling, in this study the respondents taken were 58 respondents. The level of knowledge and attitude of adolescent girls was measured using a questionnaire. Assessment of adolescent girls' knowledge using a questionnaire is categorized as “good” and “not good”. Assessment of the level of knowledge consists of 10 multiple choice questions, while the assessment of the respondent's attitude towards anemia consists of 10 questions with the options strongly agree, agree, disagree, and strongly disagree. The results of data analysis of adolescent girls' knowledge showed 66.7% of the total respondents had poor knowledge of anemia. While the attitude of adolescent girls towards anemia showed 92.6% showed a positive attitude